2014
DOI: 10.1039/c3ra46914j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of S-PCL-PDMAEMA for co-delivery of pDNA and DOX

Abstract: Similar numbers of repeating units of PCL and pDMAEMA were controlled between L-PCL-PDMAEMA and S-PCL-PDMAEMA. DOX-loaded S-PCL-PDMAEMA micelles showed a better cell-killing effect than DOX-loaded L-PCL-PDMAEMA in four cell lines. The co-delivery of DOX and pDNA was confirmed by CLSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Although researches recently show that polymer materials containing segments of PCL and PDMAEMA can be potentially used in drug delivery applications [13,15,[23][24][25][26][27][28], there is not a general consensus about the effect of their structure on their performance. The aim of this study is to establish relationships between the composition and molecular weight of triblock copolymers PDMAEMA-b-PCL-b-PDMAEMA with the colloidal properties of micelles obtained from their assembly in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…Although researches recently show that polymer materials containing segments of PCL and PDMAEMA can be potentially used in drug delivery applications [13,15,[23][24][25][26][27][28], there is not a general consensus about the effect of their structure on their performance. The aim of this study is to establish relationships between the composition and molecular weight of triblock copolymers PDMAEMA-b-PCL-b-PDMAEMA with the colloidal properties of micelles obtained from their assembly in aqueous medium.…”
Section: Introductionmentioning
confidence: 99%
“…PCL is a highly-crystallized polymer and its crystallinity increases with increasing molecular weight. This fact slows the drug release [ 22 ]. Moreover, the molecular weight of PCL of ca.…”
Section: Resultsmentioning
confidence: 99%
“…Poly( ε -caprolactone) (PCL) is an US Food and Drug Administration (FDA) approved hydrophobic polymer. It is biocompatible, biodegradable nontoxic and widely used in various biomedical applications [ 21 , 22 ]. Compared with poly (lactic acid) (PLA) and poly (glycolic acid) (PGA), PCL-based polymers have excellent properties due to its crystallinity and hydrophobicity [ 23 ], and its degradation products do not substantially lead into acidic environments [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…111 In fact, this is the most investigated biomedical application for star BCPs prepared by combination of ROP and ATRP, with several examples describing the encapsulation of hydrophobic molecules, such as doxorubicin (DOX) or paclitaxel (PTX), or even genetic material by different core-shell systems for anticancer therapy. [112][113][114][115][116][117][118][119][120][121] For example, Li and co-workers synthesized 3-and 6-arm PCL-b-PHEMA (PHEMA: Poly(hydroxyethyl methacrylate)) star BCPs by "core-first," starting with the ROP of CL followed by the ATRP of HEMA, as effective carriers for PTX delivery. 113 Results showed that drug loading and drug encapsulation efficiencies of the micelles formed in aqueous medium were influenced by both the number of arms and composition of the stars.…”
Section: Degradable Star Bcps For Drug Deliverymentioning
confidence: 99%